Are Students Prepared to Communicate? A Case Study of an Australian Degree Course in Biotechnology - Edmonston, J.; Dawson, Vaille; Schibeci, R. (Springer, 2010)
Public concerns about biotechnology have resulted in greater attention being paid to the mechanisms by which biotechnology is communicated with non-scientists, including the provision of science communication training. As undergraduate and postgraduate courses form the foundation of the biotechnology sector by providing a pipeline of university graduates entering into the profession, it has been proposed that formal science communication training be introduced at this early stage of career development. Using an Australian biotechnology degree course as a case study, this paper examines science communication training within this course and the views of past and present students towards this training. Interviews were undertaken with 22 stakeholders in the case, including undergraduate lecturers (who also supervise postgraduate research students), doctoral candidates and biotechnologists recently graduated from the course.Few of the students felt the course provided them with any form of science communication training, let alone training in how to engage non-scientists. Many were unaware of the training available to them and few of the lecturers were able to identify where communication skills are taught within the course. A previous study of this case has also shown that biotechnology undergraduates taking this course do not value communication with non-scientists. Clearly, the current state of science communication training for these students needs to be improved if they are to enter the biotechnology workforce as able civic scientists. The findings of this study may be useful for other university biotechnology courses which have yet to integrate science communication training into their curriculum.